The study of New Retail Ecosystem in People’s Republic of China: Alibaba case study - Kaewkitipong, Laddawan; Ractham, Peter (Journal of Business Administration The Association of Private Higher Education Institutions of Thailand, 2020)
New Retail is a new model of retail that was coined by Alibaba Inc to describe the online-to-offline integration for the retail industry. This research explored the New Retail Ecosystem to identify key stakeholders and their roles, and to understand digital transformation strategy and processes undertaken. This research employs the qualitative approach to explore the evolution of the new retail phenomenon in the People Republic of China. To answer the research questions, the researchers collected data via face-to-face interviews and observation through field visits. The findings reveal that in the new retail business ecosystem, Alibaba plays the main role in managing a central platform that facilitates and coordinates the linkage between the key stakeholders. The abilities to link various information systems and allows data exchange between stakeholders is the main mechanism of Alibaba’s new retail ecosystem; they also drive the stakeholders to co-evolve and adapt to form excellent new retail experiences for customers. Ultimately, the research shows how businesses in the New Retail’s ecosystem adapted and transformed to set examples for retail businesses in Thailandใ